Seni Arsitektur Bali Dalam Bangunan-Bangunan Bali (Kajian Filosofis) - Ida Ayu Devi Arini; Ida Bagus Gede Paramita (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2021)
Balinese people believe they live in the world to create goodness, which is called dharma. However, if the Balinese make mistakes, then when they die they will be reincarnated to cleanse their sins until they become one with God. This is the Balinese cosmological concept adopted in Balinese architecture. Traditional Balinese architecture is defined as a spatial layout that accommodates the life of the Balinese people who have developed from generation to generation with rules inherited from ancient times to the present. Balinese architecture is a vernacular architectural style designed using local materials to construct buildings, structures and houses, as well as reflecting local traditions Traditional Balinese architecture is inseparable from the existence of a Hindu script called Lontar Asta Kosala Kosali which contains the rules for making houses or puri and rules for places of worship or temples. In Asta Kosala Kosali it is stated that the rules for building a house must follow the anatomical rules of the house owner's body with the help of undagi as a holy person who has the authority to help build a house or temple. This paper aims to examine the philosophical aspects of Balinese buildings related to Balinese architecture; reintroducing Balinese buildings which are now becoming scarce. This is a qualitative research with a functional and philosophical approach. The data collection method is literature study. The results of the study were to determine the philosophical aspects of Balinese buildings and the tipes of Balinese buildings.Keywords: Balinese Architecture, Philosophy